The development of intensity duration frequency curves fitting constant at Kuantan River Basin - Nur Salbiah, Shamsudin (2016)
Changing in climate is one of the main parameter that affecting the water resources as it affects the whole hydrologic cycle thus cause variation in rainfall intensity, duration and frequency of precipitation. The rainfall Intensity Duration Frequency (IDF) relationship is one of the tools that is commonly used in water resources engineering, either for planning, designing and operating the water resources project. The aims of this research is to develop the fittings constants based on the intensity duration frequency (IDF) curves for Kuantan River Basin. Two frequency analysis were used to develop the IDF curve from rainfall data along Kuantan River Basin. These techniques are: Log Normal Distribution and the Normal Distribution Function. These method is used to obtain the IDF curve for twelve durations (5, 10, 15, 30, 60, 180, 360, 720, 1440, 2880, 4320and 7200) minutes. This study used Annual Maximum Series data obtained from Department of Irrigation and Drainage (DID). It consists of 10 stations along Kuantan River Basin. Derived equations for calculating rainfall intensity for Kuantan River Basin was obtain by using two technique based on result obtained from IDF data. The estimation for fittings constants of IDF curve for different return periods was performed using empirical formula. The equations are Sherman Equation and Bernard Equation. These equations are used to computed the locality constants (a, b, c). The rainfall intensity value obtain from Sherman Equation is larger compare to the rainfall intensity from Bernard Equation which is the percentage different of Sherman Equation is 10% until 700% while the percentage different of Bernard Equation is 10% until 300%. This is because the reference station that is Station 3930012 (Sg. Lembing PCCL Mill) is located at the upstream and other station were located at the downstream of the river. Thus the intensity of downstream is lower compare to the intensity at the upper stream of the river.